On the Front Lines: Helping Military Spouses Thrive in Your Community : FCS3392/FY1534, 1/2024 - Jowers, Kristen; Gillen, Martie (EDIS, 2024)
Knowing how to support military spouses in your service network can contribute to mission readiness, and help military spouses thrive in the communities you serve. This publication discusses military spouse demographics, military spouse employment, military spouse well-being including food security, financial security, and civilian community belonging, and employment resources and strategies to support military spouses. Written by Kristen Jowers and Martie Gillen, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2024.